Design and analysis of a MRI miniature for children - Muhammad Taqiuddin, Mohamad Tabarani (2010)
Magnetic Resonance Imaging (MRI) is a machine that had been used for imaging the internal section of our body by using the principal the magnetic field. In the process of the imaging, the patient must follow the instruction so they did not move along the process because it will affect the result. Children also not excluded from gone through the process. This MRI also produces very noisy sound produces loud thumping and humming noises during imaging. So, for the children, sometimes they get too frightened to get along the examination process. By using the miniature, it help to reduce and to distinguished that feeling and to avoid others parameter that will damage the examination result. The design of a MRI miniature was design in the solidworks software and being analysis by Cosmos. The result was being taken from three aspects which are stress analysis, displacement analysis, and deformation analysis. The new design of miniature could uphold the load of average children’s weight within 45kg or441.45 N.